Neuromuscular and Neuroendocrinological Features Associated With ZC4H2-Related Arthrogryposis Multiplex Congenita in a Sicilian Family: A Case Report - Gianluca Piccolo; Gianluca Piccolo; Giuseppe d'Annunzio; Elisabetta Amadori; Elisabetta Amadori; Antonella Riva; Antonella Riva; Paola Borgia; Domenico Tortora; Mohamad Maghnie; Mohamad Maghnie; Carlo Minetti; et al. (Frontiers in Neurology, 2021)
Wieacker-Wolff syndrome (WWS) is an X-linked Arthrogryposis Multiplex Congenita (AMC) disorder associated with broad neurodevelopmental impairment. The genetic basis of WWS lies in hemizygous pathogenic variants in ZC4H2, encoding a C4H2 type zinc-finger nuclear factor abundantly expressed in the developing human brain. The main clinical features described in WWS families carrying ZC4H2 pathogenic variants encompass having a short stature, microcephaly, birth respiratory distress, arthrogryposis, hypotonia, distal muscle weakness, and broad neurodevelopmental delay. We hereby report a Sicilian family with a boy clinically diagnosed with WWS and genetically investigated with exome sequencing (ES), leading to the identification of a c.593G>A (p. R198Q) hemizygous pathogenic variant in the ZC4H2 gene. During the first year of life, the onset of central hypoadrenalism led to recurrent hypoglycemic events, which likely contributed to seizure susceptibility. Also, muscle biopsy studies confirmed a pathology of the muscle tissue and revealed peculiar abnormalities of the neuromuscular junction. In conclusion, we expand the phenotypic spectrum of the WWS-related neurodevelopmental disorders and discuss the role of ZC4H2 in the context of the potential neuroendocrinological and neuromuscular features associated with this condition.